Efek Antifotoksidatif Ekstrak Andaliman (zanthoxylum Acanthopodium Dc.) terhadap Asam Linoleat - Edi Suryanto; Sri Raharjo; Harjono Sastrohamidjojo; Tranggono Tranggono (agriTECH, 2005)
Andaliman fruit is a seasoning commonly used in traditional food preparation in North Sumatera. It is also well known as a folk medicine source to cure several kind of illness. The objectives of this study were to determine effect of andaliman extract in photooxidation reaction in model systems. Andaliman was extracted sequentially with hexane, acetone and ethanol. The photooxidation reaction system was consisted of linoleic acid (0,03 M) in methanol containing 100 ppm erythrosine as a sensitizer and the reaction mixture was exposed under 4000 lux fluorescent light for up to 5 hours. Ethanol extract (EHSAE) was found to have the highest anti-photooxidative effect, followed by those of acetone extract (ESHA) and hexane extract (EH), respectively. Linoleic acid treated will ESHAE at 500 ppm concentration and 500 ppm Â±-tocopherol showed lower peroxide value compare to the control samples at 5 hours light exposure in room temperature. However, ESHAE showed any difference in it anti-photooxidative effect than that of Â±-tocopherol as a positive control (p<0.05). The study on the extracting solvent effects indicated than the antiphotooxidative components in the fruit andaliman posses stong polar property and easily extracted with polar solvent. The addition of ethanol extract (ESHAE) showed less blanching ability of erythrosine, followed by acetone extract (ESHA) and hexane extract (HE). These result suggest that the ethanolic extract of andaliman contains components having antiphotooxidative activity.